Analisis Nilai Tambah Proses Pengolahan Kopi Arabika Gayo pada Kabupaten Centra Produksi di Aceh - Emmia Tambarta Kembaren, S.P, M,Si. (Fakultas Pertanian, Universitas Timor, 2021)
Indonesia known as one of the biggest coffee exporter in the world after Brazil, Vietnam, dan Colombia. Aceh is one of the central production areas of Arabica Coffee Comodity in Indonesia. This study aims to determine the difference of Gayo Arabica coffee beans added value based on the processing in Aceh Tengah and Bener Meriah Regency. This research located in two central production of coffee in Aceh. Both Regency ware the main location for coffee production in Aceh. This research used in-depth interviews with decision makers in green been coffee agro-industry which has largest export quantity in Aceh Tengah and Bener Meriah which are Baitul Qiradh (KBQ) Baburrayyan Cooperative and Permata Gayo Cooperative as data collection method. The Respondents were the Manager of KBQ Baburrayan; Mr. Moch. Charis, S.T. and the Manager of Permata Gayo Cooperative; Mr. Jumhur, S.P. his Research used descriptive quantitative method with Hayami analysis. The result showed that the added value of labui coffee beans to green coffee beans in Aceh Tengah Regency was higher which is Rp. 28,337/kg by 38.40% ratio when compared to green bean coffee in Bener Meriah Regency which is Rp. 26,738 / kg by 37.14% ratio. This result wes caused by: (1) the price of green beans in Aceh Tengah Regency is higher than in Bener Meriah Regency, (2) the green bean production process in Aceh Tengah Regency tends to use more modern technology so that it can reduce labor costs and produce added value which higher than Bener Meriah Regency.